Automated As-built Information Modelling for Construction Monitoring with Vision Data in Liquefied Natural Gas (LNG) Plants - Chai, Jian (Curtin University, 2017)
This research aims to develop automated methods of retrieve as-built information from vision data in LNG plants and to use the developed methods to improve the productivity in the LNG industry. This research investigates class-level and further object-level interpretation of point cloud objects in LNG plants. By developing scaffolding detection methods, this research also contributes novel scaffolding construction monitoring methods using intrinsically safe cameras.